Role of Mitanin community health workers in improving complementary feeding practices under scaled-up home-based care of young children in a rural region of India - Samir Garg; Mukesh Dewangan; Kavita Patel; C Krishnendhu; Prabodh Nanda (BMC pediatrics, 2023)
The current study was aimed at assessing the coverage of home-based care of young children (HBYC) in Chhattisgarh state where it has been implemented through 67,000 rural Community Health Workers (CHWs) known as Mitanins.
Keywords: Health Policy, Community Health Services